2018
DOI: 10.3390/ijerph15122803
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Transmission in Households and Classrooms of Adolescent Cases Compared to the Community in China

Abstract: The aim of this paper is to evaluate the link between the history of exposure to tuberculosis (TB) in the household and diagnosed TB cases at school, and to compare the detection rate of active TB among household contacts and classroom contacts of adolescent TB cases with the rates among contacts of healthy controls. From November 2016 to December 2017, a prospective matched case-control study was conducted using passively identified index adolescent student cases from the TB surveillance system and healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
1
9
0
7
Order By: Relevance
“…It is not surprising, therefore, that the adolescent age group made up almost a quarter of the TB cases seen in our study. Adolescents may acquire TB either at home or from school [29] [30], most importantly, a previous study showed that having an index adolescent TB case in the classroom significantly increased the risk of classmates contacting active TB [30]. What this means is that our adolescent TB patients acted like a reservoir for the transmission of the disease in their schools, supporting the inclusion of schools in TB screening programmes.…”
Section: Discussionmentioning
confidence: 55%
“…It is not surprising, therefore, that the adolescent age group made up almost a quarter of the TB cases seen in our study. Adolescents may acquire TB either at home or from school [29] [30], most importantly, a previous study showed that having an index adolescent TB case in the classroom significantly increased the risk of classmates contacting active TB [30]. What this means is that our adolescent TB patients acted like a reservoir for the transmission of the disease in their schools, supporting the inclusion of schools in TB screening programmes.…”
Section: Discussionmentioning
confidence: 55%
“…A case-control study conducted in Ethiopia has shown that individuals that had a TB household member had an increased risk of developing TB by 3-fold [15]. Systematic TB contact tracing at the household level is not only an effective method to detect secondary cases of TB but the method is also an important epidemiologic tool to understand the transmission dynamics and prognostic factors of TB transmission in households [16,17]. Commonly used TB surveillance methods include a questionnaire survey, tuberculin skin test (TST) and chest imaging examination of household contacts of tuberculosis patients [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the World Health Organization (WHO) End TB Strategy, systematic screening of contacts including children will be important. [3] Therefore, more epidemiological evidence is needed on the risk of infection and disease especially among populations at high risk, such as children, in order to guide future policy development for screening and preventive therapy.…”
Section: Introductionmentioning
confidence: 99%